Analisis Kinerja Keuangan Dengan Menggunakan Rasio Likuiditas, Solvabilitas Terhadap Rasio Profitabilitas PT. Unilever Indonesia Tbk, (UNVR) Dan PT. Indofood Sukses Makmur Tbk, (INDF) Periode 2021-2022 - Wahyu Setiawan; Hasnaa Rizky Putri Q; Sri Hermuningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to analyze the comparative financial performance of PT Unilever Indonesia Tbk, (UNVR) and PT Indofood Sukses Makmur Tbk, (INDF) on the Indonesia Stock Exchange for the period 2021-2022. The research methodology used is a qualitative descriptive method with a case study type of research. The type of panel data (time series and cross section) comes from secondary data from the Indonesia Stock Exchange. The sampling technique used purposive sampling method with annual data from 2014-2018. The data was analyzed using a qualitative comparison of the company's financial performance through a comparative approach with liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The results showed that the liquidity ratio (CR) of INDF had better performance than UNVR. The liquidity ratio (QR) of INDF has better performance than UNVR. The solvency ratio (DAR) of INDF companies has better performance than UNVR. The solvency ratio (DER) of INDF companies has better performance than UNVR. Based on the profitability ratio (ROA) the UNVR company has better performance than INDF. profitability (ROE) the UNVR company has better performance than INDF.